(untitled) (UNWE Yearbook, 2009)
The main objective of this paper is to present the nature, characteristics and structural components of Business Intelligence Systems (BIS). Figure out are some of the important factors that could lead to the successful BIS establishment. The Roadmap Methodology of Business Intelligence Systems Design and Development is described with all the stages and steps of the process. Tree parallel paths are presented as successful approach to an effective BIS establishment within the organization. One of the most difficult tasks of BIS development is to select the appropriate architecture. The visions for an effective BI architecture of three leading companies in the field are described and some of the main difficulties within this procedure are figure out. Outlined are the major considerations that should be taken into account in order to select the appropriate architecture for the organization’s BIS development. The BIS current advantages and main directions of their future development are given in the conclusion.